Investigation of FCVs durability under driving cycles using a model-based approach. (February 2020) - Han, Jaeyoung; Han, Jaesu; Yu, Sangseok
Highlights: A stack degradation model is developed that can predict the stack durability. A degradation model is developed from experimental data using DOE. A degradation fuel cell model is implemented in the vehicle dynamics. A fuel cell vehicle model is carried out to evaluate the stack durability under various cycles. By driving mode comparison, urban mode is proven to be more effective for stack durability. Abstract: The stack degradation of a fuel cell system is a critical factor in ensuring the stack performance and reliability of a fuel cell vehicle (FCV). In particular, the stack degradation depends strongly on the proton-conductive ability in the membrane during vehicle operating. This study presents an effective degradation FCV model along with a degradation predictive model for various driving cycles. The stack degradation is indicative of the water content term, which is strongly dependent on the membrane conductivity term. The stack degradation model was designed using design of experiment (DoE), and the designed fuel-cell model is validated using the experimental data. The proposed fuel cell model is also integrated into a dynamic vehicle model. The FCV model is simulated to investigate its transient behaviors during various driving cycles. The transient responses of the vehicle speed, demanded fuel cell power, and water content are properly captured. To evaluate the degradation rate of the FCV under various driving cycles, the scenarios of time and distance are applied, and the tradeoffs are investigated based on the degradation of the FCV model over a range of durations and current densities. For a low running distance, an urban dynamometer driving schedule is more effective than the other cycles. Further, with an increase in the running distance, the aggressive driving (US06) cycle requires more energy compared to the other cycles. Our results confirmed that the designed FCV model can be used to predict the degradation of a fuel cell stack under various driving cycles without a real test bench.